The politics of linking schools and social services - Adler, Louise; Gardner, Sid (Education policy perspectives., 1995)
Over the years, arguments have been raised for and against linking schools and social services, and the merits or otherwise of each system. This volume brings together research and public policy issues to focus on the new framework of service provision.